Development of Research-based Yoga Module for Bronchial Asthma - Sarda, Aditi (International Research Journal of Ayurveda & Yoga, 2025)
Asthma is a common, paroxysmal, and reversible respiratory disorder affecting millions of people worldwide. It is necessary to find a healthy and feasible method/technique to manage the disorder in every age group and levels of asthma. Yoga is a holistic therapy as it is a combination of ᾱsanas, pranᾱyᾱma, mudra, and dhyᾱna. It works on excellence of every aspect of life, being physical, mental, social or spiritual. It helps in creating balance between the sympathetic and parasympathetic nervous system, as research shows. A research review has been planned using a PICO search strategy to explore the effect of Yogᾱ on asthma and to develop a research-based yoga module to help patient get rid of the disorder and manage their symptoms. The inclusion and exclusion criteria were applied for the search strategy from the year 2010 to 2022, population aged between 10 and 60 years, and yoga as the primary intervention having randomized controlled trial as the research methodology. The four-step analysis process was applied to the filtration of the researched articles. 09 articles were found eligible for review. These studies showed a positive link between yoga and asthma. The major findings imply that yoga has a significant positive impact on pulmonary functions and the quality of life of asthma patients.